Role of Helicopter Transfer and Cloud-Type Imaging for Acute Type A Aortic Dissection - Ishikawa, Natsuya; Narita, Masahiko; Shirasaka, Tomonori; Ushioda, Ryouhei; Tsutsui, Masahiro; Azuma, Nobuyoshi; Kamiya, Hiroyuki (The Thoracic and Cardiovascular Surgeon, 2023)
Background This study explored if long-distance transfer was safe for patients suffering from acute aortic dissection type A (AADA) and also analyzed the effectiveness of helicopter transfer and cloud-type imaging transfer systems for such patients in northern Hokkaido, Japan.Methods and Results The study included 112 consecutive patients who underwent emergency surgical treatment for AADA from April 2014 to September 2020. The patients were divided into two groups according to the location of referral source hospitals: the Asahikawa city group (group A, n = 49) and the out-of-the-city group (group O, n = 63). Use of helicopter transfer (n = 13) and cloud-type telemedicine (n = 20) in group O were reviewed as subanalyses.Transfer distance differed between groups (4.2 ± 3.5 km in group A vs 107.3 ± 69.2 km in group O; p = 0.0001), but 30-day mortality (10.2% in group A vs 7.9% in group O; p = 0.676) and hospital mortality (12.2% in group A vs 9.5% in group O; p = 0.687) did not differ. Operative outcomes did not differ with or without helicopter and cloud-type telemedicine, but diagnosis-to-operation time was shorter with helicopter (240.0 ± 70.8 vs 320.0 ± 78.5 minutes; p = 0.031) and telemedicine (242.0 ± 75.2 vs 319.0 ± 83.8 minutes; p = 0.007).Conclusion We found that long-distance transfer did not impair surgical outcomes in AADA patients, and both helicopter transfer and cloud-type telemedicine system could contribute to the reduction of diagnosis-to-operation time in the large Hokkaido area. Further studies are mandatory to investigate if both the systems will improve clinical outcomes.
Keywords: acute aortic dissection type A; long-distance transfer; helicopter; telemedicine